2010
DOI: 10.1017/s1047951109992009
|View full text |Cite
|
Sign up to set email alerts
|

Associations between being overweight, variability in heart rate, and well-being in the young men

Abstract: Abnormalities of the autonomic nervous system have been repeatedly shown in hypertension. We studied the associations between being overweight, blood pressure, cardiac vagal tone as measured by variability in heart rate, and well-being in a large cohort of young men. We hypothesised an inverse correlation between body mass index and the variability in heart rate. Further, we assessed systolic and diastolic blood pressure as traditional indicators of cardiovascular risk. Exclusion criteria were the use of drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
11
2
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
5
11
2
5
Order By: Relevance
“…BMI could play a key role in the pathogenesis of prehypertension. Earlier studies conducted indicated that higher BMI could be an independent contributing factor for vagal withdrawal and sympathetic overactivity among the prehypertensives [17,18]. Furthermore, WC is reported to have a strong association with the development of hypertension [19] and in our study, both WC and HC were significantly increased among the prehypertensives group.…”
Section: Discussionsupporting
confidence: 69%
“…BMI could play a key role in the pathogenesis of prehypertension. Earlier studies conducted indicated that higher BMI could be an independent contributing factor for vagal withdrawal and sympathetic overactivity among the prehypertensives [17,18]. Furthermore, WC is reported to have a strong association with the development of hypertension [19] and in our study, both WC and HC were significantly increased among the prehypertensives group.…”
Section: Discussionsupporting
confidence: 69%
“…There is no consensus about the relationship between obesity and ANS activity level. The opposite hypothesis that most obese subjects are low in sympathetic activity (the MONA LISA hypothesis) [10] was also confirmed by some studies [9,11]. …”
Section: Introductionmentioning
confidence: 66%
“…Obesity may alter the balance between the sympathetic and parasympathetic nervous system [9]. There is no consensus about the relationship between obesity and ANS activity level.…”
Section: Introductionmentioning
confidence: 99%
“…This finding supports the notion that distribution of free time is an important factor for maintaining health when working a rapidly rotating, clockwise shift schedule. Numerous factors may affect the sleep-related cardiac autonomic system, such as age 15) , BMI 27) , blood pressure 28) , tea/coffee consumption 29) , and sleep patterns 25) . In the present sample, no differences were present between the control and experimental groups regarding age, BMI, the number of years employed in nursing, blood pressure, and tea/coffee consumption.…”
Section: Discussionmentioning
confidence: 99%